Hubungan Keseimbangan Tubuh dengan Resiko Jatuh pada Lansia di Rumah Pelayanan Sosial Lansia Pucang Gading Semarang - Lisa Septi Meilinda Putri; Iskim Luthfa; Moch.Aspihan (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Background: When someone falls, they quickly lay down or sit down on the ground or floor, whether they are aware of it or not. Many older people experience falling as a normal part of getting older. One in three older people will fall at least once a year, and half of those people have fallen more than once in the past. There are many things that can make an older person more likely to fall. These include sociodemographic factors like age, gender, and socioeconomic status, physiological factors like neuromuscular, musculoskeletal, visual, vestibular, proprioceptive, biomechanical, muscle strength, balance, and gait pattern, medical conditions (pathological), environment, and psychological factors. Aminia et al. (2022) say that anxiety and fear of falling are mental disorders that happen to older people. Mhetod: A pre-experimental research design with a one-group pretest and post-test design, a purposive sampling technique, and 14 people who filled out an observation sheet. Findings: This research shows that there is a link between older people's body balance and their risk of falling. A P value of 0.000, which is less than 0.05, was found in the study used Gamma correlation. Because the 0.000 P number is less than 0.05, there is a link. Conclusion: There is a significant relationship between body balance and the risk of falling in the elderly at the Pucang